Analisis Gradasi Butiran Limbah Rubber Deposit Runway (LRDR) sebagai Pengganti Agregat Halus pada Campuran Beton - Viktor Suryan; Virma Septiani; Dwi Cahyono; Ria Maya Sari; Amira Erinda Khoirunisa Lesmana; Karina Nabila Maharani; Anggi Nidya Sari (Universitas Batanghari Jambi, 2026)
Rubber deposit waste generated from aircraft tire abrasion on airport runways has potential as a substitute material for fine aggregate in concrete mixtures, in line with the need to reduce dependence on natural aggregates whose extraction can damage ecosystems. This study aims to analyze the grain characteristics of rubber deposit waste compared to sand as a conventional fine aggregate, as a preliminary feasibility study for its use in concrete mixtures. The research employed a quantitative method with an experimental approach through sieve analysis testing using a Sieve Shaker, with three repetitions for each material, followed by comparative analysis. The results show that, visually, rubber deposit waste appears darker than sand due to its material content, which mostly originates from the abrasion of aircraft rubber tires. The sieve analysis results indicate that rubber deposit waste generally has finer grains than sand, marked by a passing percentage on the 0.425 mm sieve of 66.91% compared to 26.72% for sand, and a much higher content of very fine particles (passing the 0.075 mm sieve), namely 11.01% compared to 0.49% for sand. This gradation difference indicates that rubber deposit waste has potential as a partial substitute for fine aggregate, although its high fine-particle content needs to be further considered in relation to water demand and the workability of the concrete mixture. This study provides a basis for further research on the effect of rubber deposit waste substitution on the physical and mechanical properties of concrete.